Real-time PCR investigation of the prevalence of Fusobacterium necrophorum in patients with pharyngitis in Japan. Issue 12 (December 2018) - Hayakawa, Kayoko; Nagashima, Maki; Kanehisa, Eriko; Watanabe, Riri; Kunimatsu, Junwa; Ohta, Kaichi; Mutoh, Yoshikazu; Hashimoto, Takehiro; Katanami, Yuichi; Yamamoto, Kei; Kutsuna, Satoshi; Tayama, Niro; et al.
Abstract: Purpose: Recent data suggest an association between Fusobacterium necrophorum infection and pharyngotonsillitis among adolescents and adults. However, existing reports are only from North America and Europe. We aimed to identify and compare the prevalence of F. necrophorum among patients with pharyngitis and asymptomatic controls in Japan and clarify the epidemiological characteristics of pharyngitis. Methods: Patients aged ≥16 years with pharyngitis and asymptomatic controls were prospectively included. F. necrophorum was detected by using both conventional culture methods and real-time F. necrophorum -specific PCR targeting the rpoB gene. The prevalence of β-hemolytic streptococci was also identified and compared between groups. Results: Forty-four pharyngitis patients and 31 asymptomatic controls were included. F. necrophorum was identified using PCR in 6 (13.6%) pharyngitis cases and 2 (6.5%) controls, with no significant difference (p = 0.457). The median bacterial load of F. necrophorum identified with real-time PCR was significantly higher in pharyngitis cases than in controls (p = 0.046). Patients with a high Centor Score tended to have a higher bacterial load than those with a low Centor Score and controls. In cases of pharyngitis, the prevalence of F. necrophorum was similar to that of Streptococcus pyogenes ( F. necrophorum -positive: 6 [13.6%] vs. S. pyogenes -positive: 5 [11.4%], p = 0.99). Conclusion: F. necrophorum was similarly prevalent among pharyngitis cases as S. pyogenes in Japan. The association of higher F. necrophorum bacterial load with symptomatic pharyngitis in accordance with the previous findings from a different geographical region suggests that F. necrophorum is an important causative agent of bacterial pharyngitis.